Proposed digital scanning parameters for digital masters of still photographs - Codamon, Kevin Constantine A. (2002)
The creation of a digital master preserves the most information captured from a physical source. Derivative images for purposes such as on screen display, image databases and online libraries can be then extracted from the digital master. The process of converting physical photographs to a digital form requires uniform scanning parameters in order for it to become efficient without sacrificing quality. With this in mind, what are the steps to be taken in order to come up with scanning parameters for digital masters of still photographs?